Peripheral polyneuropathy in patients receiving long-term statin therapy - Ibrahim Halil Özdemir; Özge Copkiran; Hakan Tıkız; Canan Tıkız (KARE Publishing, 2019)
Objective: Peripheral neuropathy is an important potential side effect of statin use. This study was an investigation of the incidence of peripheral neuropathy in patients taking atorvastatin or rosuvastatin for hypercholesterolemia and the relationship to the dose and duration of the treatment. Methods: In all, 50 patients using a statin treatment and 50 healthy controls matched for age and gender who had never taken a statin were included in the study. Polyneuropathy was assessed with a neurological examination and electroneuromyography (ENMG). Results: While no polyneuropathy was detected in the control group, polyneuropathy was seen in 33 (66%) of the patients in the statin group (p<0.01). There was no significant difference between the 2 statin groups in the results of the neurological examination or the ENMG findings regarding the incidence of polyneuropathy (p=0.288 and p=0.720, respectively). Neuropathy was observed in a neurological examination performed within the first year in 50% of the rosuvastatin users and 18% of those taking atorvastatin. The severity of the polyneuropathy increased with the duration of the treatment in the atorvastatin group (p=0.030). Conclusion: This study revealed an increased risk of peripheral neuropathy with long-term statin use (>1 year). Electrodiagnostic changes have been detected in motor and sensory nerves in nerve conduction studies of patients on long-term statin treatment. The assessment of neurological symptoms, like tingling, numbness, pain and tremor in the hands and feet, and unsteadiness during walking associated with peripheral neuropathy may be useful in the follow-up of the patients on long-term statin treatment. Early detection of peripheral neuropathy and changing hypercholesterolemia treatment may prevent permanent nerve damage.